Analysis of The Effectiveness of Sediment Control Structures and River Improvement on The Omu River Post-Earthquake in Sigi Regency - Putranto, Angga Eko; Adityawan, Mohammad Bagus; Moerwanto, Arie Setiadi; Natakusumah, Dantje Kardana (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2024)
This study aims to analyze the effectiveness of sediment control structures, such as sabo and consolidation dams, and river normalization on sediment control in the Omu River after the earthquake in Sigi Regency on September 28, 2018. The analysis was conducted using the Universal Soil Loss Equation (USLE) method based on average rainfall data over 20 years. Erosion and sedimentation volumes before and after the earthquake were analyzed to understand the changes. The results showed that in 2020, the erosion volume reached 120,700.27 m³/year, and sedimentation was 17,030.81 m³/year, an increase from 2017, which recorded an erosion volume of 91,282.60 m³/year and sedimentation of 12,879.97 m³/year. Sediment transport simulation with daily discharge over 12 years indicated that in Scenario-1, sediment could be reduced by 10.81%, and in Scenario-3 by 23.18%. Meanwhile, simulation with Q100 flood discharge in Scenario-2 showed sediment reduction by 47.18%, and in Scenario-4 by 62.96%. The general conclusion of this study is that sediment control structures and river normalization are effective in reducing sediment volumes. Specifically, the construction of sediment control structures has proven to significantly reduce erosion and sedimentation. This research highlights the importance of structural improvements in mitigating post-disaster erosion impacts. The results of this study can serve as a reference for planning and implementing sediment control in disaster-prone areas. Keywords: sediment control, sabo dam, consolidation dam, river normalization, Omu river